Електронні технології підготовки бібліографічної інформації - Тодорова, Є. М. (ХДАК, 2015)
Розглядаються технологічні особливості процесу бібліографування в електронному середовищі. Наголошується на необхідності відповідності бібліографічних технологій інформаційним потребам суспільства і рівневі комп’ютеризації всіх галузей людської діяльності. Розвиток електронної бібліографії, упровадження сучасних інформаційних технологій у бібліографічну роботу бібліотек потребують відповідних змін у процесі підготовки бібліографічної інформації. Підкреслюється, що поширення електронної бібліографії є важливим засобом прогнозування подальшої еволюції бібліографічних технологій.

The paper deals with the technological features of bibliography in electronic environment. The author focuses on the fact that bibliographic technologies should correspond to the information requirements of the society and the level of computerization of all areas of human activities. Development of electronic bibliography, implementation of the up-to-date information technologies into the bibliographical work of libraries require corresponding changes in the process of preparation of bibliographic information. It is proved that dissemination of the electronic bibliography is an important way for prognosis of the future evolution of bibliographic technologies.
Keywords: бібліографічна інформація; бібліографія електронна